In plane Shear Strengthening of Clay Masonry Walls with Opening - Sarwat Hassan Ahmed; Muhammad Raouf Abdulkadir (Sulaimani Journal for Engineering Sciences, 2020)
In this paper, results of testing eight clay brick wall specimens are presented. Seven of the walls contained opening and one wall without opening. The walls were tested under constant uniformly distributed vertical load and gradually increased lateral load. Six walls were strengthened using the following techniques: reinforced concrete frame around the opening, reinforced concrete frame around the opening with the beam extended to the ends of the wall, steel channel frame inside the opening, reinforced concrete frame confining the boundary of the wall (outside confinement), near surface mounted strengthening with (4) mm steel bar and strengthening with ferro-cement. The test results illustrated that walls strengthened with external frame showed increased lateral load carrying capacity, ductility and toughness compared to non-strengthened wall, and all other strengthened walls showed different ranges of increased shear strength capacity. However, the wall strengthened with ferro-cement did not improve the ultimate lateral load carrying capacity but ductility significantly improved. For the wall strengthened with near surface mounted steel bars, the ultimate lateral load carrying capacity dramatically increased but the lateral displacement did not increase notably.